Criminal genius: a portrait of high-IQ offenders - Oleson, James C. (University of California Press, 2016)
"This study provides some of the first empirical information about the self-reported crimes of adults with genius-level IQ scores. The study combines quantitative data about 72 different offenses with qualitative data from 44 follow-up interviews to describe nine different types of offending: violent crime, property crime, sex crime, drug crime, white-collar crime, professional misconduct, vehicular crime, justice system crime, and miscellaneous crime"--Provided by publisher